2020
DOI: 10.3389/fcomp.2020.00039
|View full text |Cite
|
Sign up to set email alerts
|

Deriving a Cortisol-Related Stress Indicator From Wearable Skin Conductance Measurements: Quantitative Model & Experimental Validation

Abstract: In order to find a stress indicator that can be used to monitor stress with wearables, we compare the almost instantaneous effects of psychological stress on skin conductance, with the effects on the stress hormone cortisol, peaking about 20-30 min later. We modeled this relation deploying a convolution of the height of the skin conductance peaks with the cortisol stress response curve, and used it to determine a skin conductance-derived estimate of stress-induced cortisol. We then conducted a first experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Pre-Processing. EDA data were preprocessed similarly to an approach by Westerink et al (2020), using the PyPhysio package (Bizzego et al, 2019). The EDA signals were resampled at 10 Hz, and a 10 Hz Butterworth filter was applied to remove wideband noise.…”
Section: Computationally Identifying Cbsmentioning
confidence: 99%
“…Pre-Processing. EDA data were preprocessed similarly to an approach by Westerink et al (2020), using the PyPhysio package (Bizzego et al, 2019). The EDA signals were resampled at 10 Hz, and a 10 Hz Butterworth filter was applied to remove wideband noise.…”
Section: Computationally Identifying Cbsmentioning
confidence: 99%
“…Therefore, the results suggest that at the beginning of a cognitive and functional decline, cortisol levels are not elevated; however, they may increase as the disease progresses. The majority of studies, including ML, evaluated cortisol levels as an outcome, not a feature [ 54 ]. However, few studies included cortisol levels in ML algorithms able to predict different diseases, such as mental disorders [ 55 ], stress and dietary intake [ 56 ], and quality of life [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among other affective states, stress was recently investigated by Westerink et al [17]. In their study, they demonstrated a correlation between peaks of cortisol, which is the hormone associated with the experience of psychological stress, and peaks of skin conductance, thus suggesting that peaks in the EDA signal can be successfully used to identify stress episodes.…”
Section: Background and Related Workmentioning
confidence: 96%
“…We compute EDA peaks using the same tool, which implements a method capitalizing on the 1st derivative of the signal curve. The choice to include identification of signal peaks is informed by findings by Westerink et al [17], demonstrating that stressful events are associated to EDA peaks.…”
Section: Data Processing and Cleaningmentioning
confidence: 99%